Computer vision based employee activities analysis - Hoque, Md. Rezwanul; Karim, Nabil Tahmidul; Rozario, Saikat Lawrence; Md. Rumman Bin Ashraf (Department of Computer Science and Engineering, BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2013.